Results based aid: limitations of new approaches - Stephan Klingebiel (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
In the current development debate, so called results based approaches play an important part. There are two aspects to this debate: On the one hand, further improving the effectiveness of development cooperation (aid) is important to the specialists, whereas on the other hand many donors (parliaments, the public etc.) continue to call for the justification of aid expenditures. This creates great pressure to give the most concrete evidence for the utility of aid budgets. It is important to distinguish between (i) Results-Based Aid (RBA) and (ii) Results-Based Service elivery (RBSD). Even if both approaches are based on the same rationale (incentives), they are fundamentally distinct. The current international debate is focused mainly on results based aid. Results based aid aims to identify outputs or outcomes that can be measured and quantified, i.e. results that can be directly linked to development activities. A contract between the donor and partner country stipulates that for every incremental success a set amount (reward”) will be paid. So far, there is only limited experience with such approaches in practice. Sometimes they are a refinement of performance based budget supports, but in other cases it has been suggested to incentivise single successes (i.e. pay per pupil finishing school). As attractive as this approach seems, its practical implementation might turn out to be difficult. There is a great risk of creating misincentives, because all the available resources might be focused on achieving just the one goal. The following conclusions can be drawn: Some of the current instruments already offer useful ways of incentivising performance. For instance, designing budget support with variable tranches. With respect to other RBA approaches (such as Cash on Delivery), practical experience is still lacking. It is possible that the disadvantages might outweigh the advantages. The hoped for benefit of RBA approaches, that of being able to produce clearly verifiable results may only “seem to be” achievable. RBA approaches assume a clear performance orientation in the partner countries, which applies to the reform dynamic countries, but those without good governance may be less easily encouraged by such a system of incentives, and thus other approaches might bemore suitable there.
Keywords: 330